Perkembangan Teknologi Pakan Ikan Otomatis dalam Perikanan Modern : Tinjauan Literatur - Putri, Diana Eka (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2023)
The development of technology in the era of the industrial revolution 4.0 is currently increasingly sophisticated, with its rapid progress making it easier for humans to do their work. One of the advances in current technology is its ability to run a tool automatically. Automation also plays an important role in the field of fish farming, where businesses are challenged to innovate in the face of the industrial revolution. The concept of modern fish farming involves automatic feeding based on a predetermined time. This allows fish farm owners to feed regularly and consistently. The research method used is a systematic literature review, by collecting data from the Google Scholar database. By using the keywords (